Forecasting the Inflation Rate in Central Java Using ARIMA Model (Efficient: Indonesian Journal of Development Economics, 2022)
One of the important aspects of the economy is the maintenance of prices in general. Indonesia's economy is still mostly focused on Java Island, one of which is Central Java. This study aims to analyze the projection of inflation rate in Central Java in the future by using the Box Jenkins method or what is called the Auto-Regressive Integrated Moving Average (ARIMA). The data used is monthly time series inflation data in the period January 2016 - April 2021 which is obtained from the Central Java Province Statistics Agency. The analysis conducted in this study, it shows that the best model is ARMA (3,0,3) or AR (3) and MA (3). The results show that inflation will tend to increase in the next few months. In the future, it is estimated that Bank Indonesia will continue to implement an expansionary monetary policy to stimulate the economy and achieve the inflation target, which is currently still low. Salah satu aspek penting dalam perekonomian adalah terjaganya harga-harga secara umum. Perekonomian Indonesia masih banyak bertumpu di Jawa Tengah. Penelitian ini bertujuan untuk menganalisis proyeksi laju inflasi di Jawa Tengah ke depannya dengan menggunakan metode Auto Regressive Integrated Moving Average (ARIMA). Data yang digunakan adalah data inflasi runtut waktu (times series) bulanan dalam kurun waktu Januari 2016 – April 2021 yang diperoleh dari Badan Pusat Statistik Provinsi Jawa Tengah. Dari analisis yang dilakukan dalam penelitian ini menunjukkan bahwa model terbaik adalah ARMA (3,0,3 ) atau AR (3) dan MA (3) dengan stasioneritas pada tingkat level. Hasil penelitian menunjukkan bahwa inflasi akan cenderung meningkat dalam beberapa bulan ke depan. Ke depan, Bank Indonesia diperkirakan akan terus menerapkan kebijakan moneter ekspansif untuk mendorong perekonomian dan mencapai sasaran inflasi yang saat ini masih rendah.